Zur Simulation des Rad-Schiene-Verschleißes bei Straßenbahnen - Heck, Jennifer (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2016)
In the present work, a methodology for the reliable simulation of wheel-rail wear of trams is developed and applied to relevant operating conditions. The methodology combines a multibody vehicle-dynamics simulation, a dynamic contact simulation based on FEM, and a wear calculation. The results show that the maximum friction energy density in very tight track curves is significantly higher compared to heavy rail systems. The sensitivity of the considered influence parameters on wear is assessed.